2021
DOI: 10.1109/temc.2021.3051100
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Cavity Resonance Equalization With Bandpass Negative Group Delay

Abstract: This paper deals with an original equalization method of 3-D electromagnetic (EM) cavity resonance by using bandpass negative group delay (NGD) function. Based on the equivalent circuit, the S-matrix model of the equalized EM cavity is introduced. The design equations of the NGD function are established in function of the cavity physical parameters. The feasibility of the equalization method is validated with a 42×28×3.8 cm rectangular cavity containing two communicating monopole antennas. By considering the T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…The proposed BP NGD circuit can be used for many potential applications in the future: Against the GD effects in the RF, wireless, and telecommunication systems as phase shifter design (Wan, Ji and Ravelo, 2019) And the resonance effect reduction in the PCB and also for the avoidance of EMC effect (Nebhen & Ravelo, 2021; Ravelo, Lalléchère, et al., 2021; Ravelo,Wan, Nebhen, et al., 2021). …”
Section: Discussionmentioning
confidence: 99%
“…The proposed BP NGD circuit can be used for many potential applications in the future: Against the GD effects in the RF, wireless, and telecommunication systems as phase shifter design (Wan, Ji and Ravelo, 2019) And the resonance effect reduction in the PCB and also for the avoidance of EMC effect (Nebhen & Ravelo, 2021; Ravelo, Lalléchère, et al., 2021; Ravelo,Wan, Nebhen, et al., 2021). …”
Section: Discussionmentioning
confidence: 99%
“…And the reduction technique of resonance effect for the electromagnetic compatibility application (Ravelo et al, 2021a(Ravelo et al, , 2021b(Ravelo et al, , 2021c.…”
Section: Discussionmentioning
confidence: 99%
“…Because of its intriguing property, the NGD effect attracts the attention of RF and microwave design engineering researchers (Siddiqui et al, 2003;Markley and Eleftheriades, 2010;Al-Bawri et al, 2020;Monti and Tarricone, 2009;Bukhman and Bukhman, 2004;Ahn et al, 2009;Chaudhary and Jeong, 2016;Sanchez-Soriano et al, 2018;Bridges, 2011a, 2011b;Ravelo, 2014aRavelo, , 2014b and (Wang et al, 2018;Chaudhary and Jeong, 2015;Das et al, 2018;Bridges, 2011a, 2011b;Zhang et al, 2017;Wan et al, 2018;Zhou et al, 2020;Ravelo et al, 2021aRavelo et al, , 2021bRavelo et al, , 2021c. Significant development of NGD Bandpass NGD investigation microwave circuits has been made with various structures (Siddiqui et al, 2003;Markley and Eleftheriades, 2010;Al-Bawri et al, 2020;Monti and Tarricone, 2009;Bukhman and Bukhman, 2004;Ahn et al, 2009;Chaudhary and Jeong, 2015;Sanchez-Soriano et al, 2018;Bridges, 2011a, 2011b;Ravelo, 2014aRavelo, , 2014b and (Wang et al, 2018;Chaudhary and Jeong, 2015;Das et al, 2018;Bridges, 2011a, 2011b;Zhang et al, 2017;.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimal value of the FoM is obtained from the derivation with respect to the minimal magnitude: (38) It can be analytically demonstrated that the derived magnitude optimal value is equal to: (39) Substituting this last value into equation (37), we obtain the maximum value of FoMn equal to: (40)…”
Section: B Optimal Value Of Bp Ngd Fommentioning
confidence: 99%